Health-related quality of life among older patients following an emergency department visit and emergency department-to-home coaching intervention: A randomized controlled trial. (December 2017) - Hall, Allyson G; Schumacher, Jessica R; Brumback, Babette; Harman, Jeffrey S; Lutz, Barbara J; Hendry, Phyllis; Carden, Donna
Introduction: Many older patients experience repeated emergency department visits and hospitalizations and inadequate links to primary care. This fragmented care can result in anxiety, uncertainty, and poor health outcomes. This study compares the impact of an emergency department-to-home coaching intervention to usual, post-emergency department care on patient-reported health-related quality of life measures: information support, anxiety, and physical function. Methods: This was a randomized controlled trial. Seven hundred and forty-nine chronically ill older adults presenting to emergency departments were randomized into Intervention (emergency department-to-home coaching) or Usual Care groups. Participants completed baseline, in-person and follow-up, telephone surveys. Within- and between-group differences in health-related quality of life were assessed using unweighted linear regression and propensity-weighted difference-in-difference analyses. Three Patient Reported Outcomes Measurement System measures were assessed: social health (informational support), mental health (anxiety/emotional distress), and physical health (physical functioning). Results: Usual Care participants experienced statistically significant declines in informational support in unweighted (−3.13) and weighted (−2.84) analyses not observed in the Intervention group (−0.91 and −1.45, respectively). Self-reported anxiety was lowest and physical function highest at the time of emergency department visit. Patient-reported anxiety increased and physical function declined statistically significantly in Intervention participants. Conclusion: Among older emergency department patients, health-related quality of life was highest at the emergency department visit and declined following the encounter. The emergency department visit per se appears to provide needed information, and in the short term, reassurance about patients' medical conditions. The coaching intervention blunts the fall in informational support observed after usual, post-emergency department care but may heighten patients' anxiety and awareness of chronic health conditions.